Analysis of moist convective instability over Indian monsoon region and neighbourhood (MAUSAM, 2003)
The nature of deep convection over the Indian monsoon region and neighbourhood during different seasons is investigated by analysing Dry Static Energy (DSE), Moist Static Energy (MSE), Precipitable Water Content (PWC) and Convective Available Potential Energy (CAPE) computed from 13 years (1982-1994) monthly mean data obtained from the National Centre for Environmental Prediction (NCEP) reanalysis.  It is seen from this study that the mean atmosphere over the Indian monsoon region is convectively unstable at lower levels during all seasons with highest degree of instability and maximum PWC during the monsoon season compared to other seasons. The results also show that during the monsoon season from June to September the convectively most unstable region is situated over the Head Bay of Bengal (HBOB) region and decreases gradually from West Pacific (WP), Equatorial South Indian Ocean (ESIO) and to Arabian Sea (AS) regions.  Similarly the CAPE value is also highest over HBOB region and it is about 362 Joules/kg (24%) more than the CAPE value over WP region.  The composite MSE profiles for strong and weak monsoon years indicate higher values of MSE at all levels during the strong monsoon years compared to weak monsoon years.  It is also observed that the surface MSE and PWC over Indian monsoon region during June to September show significant positive correlation with All India Summer Monsoon Rainfall (AISMR).